Hot methanol extract of Leea macrophylla (Roxb.) manages chemical-induced inflammation in rodent model - Hossain, Kazi Helal; Rahman, Md Atiar; Bakhtiar, M. Taher; Tangpong, Jitbanjong; Hajjar, Dina; Alelwani, Walla; A. Makki, Arwa; Ali Reza, A. S. M. (Elsevier, 2020)
Objective: This study investigated how a chemical-induced analgesia and inflammation could be managed by hot methanol extract of Leea macrophylla (Roxb.) root (LM). Methods: Nature of secondary metabolites and the phytochemicals was studied by the established qualitative tests and GC–MS analysis. The analgesic potential was tested by acetic acid-induced writhing model, formalin test and tail immersion model. In contrast, carrageenan and histamine-induced paw edema models were applied to estimate the impact on inflammatogenic agents in Wistar albino rats. Results: The LM was found to contain cardiac glycosides, flavonoids, tannins and triterpenoids. A list of about thirty compounds from the GC–MS study of LM has been recorded. The LM significantly (p < 0.05) minimized the writhing responses in acetic acid-induced writhing assay. The LM100 (LM 100 mg / kg b.w.) and LM200 (LM 200 mg / kg b.w.) reduced the licking period both in early and late phases of formalin-induced animal studies. The LM50 (LM 50 mg/kg b.w.) demonstrated the analgesic effects at 180 min, and in the tail immersion test diclofenac sodium displayed a substantial latency time at 120 and 150 min. The paw edema inhibition of LM100 and LM200 was statistically significant compared to diclofenac sodium of carrageenan-induced test. Also, the paw edema size in histamineinduced paw edema model was significantly decreased by LM50. Conclusion: Results demonstrated that L. macrophylla (Roxb.) root extract could be very potential source of therapeutic formulation in pain and inflammation with further clarification.